TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK PENJUALAN SKINCARE RACIKAN DOKTER TANPA IZIN EDAR BPOM: STUDI KASUS KONSUMEN GEN Z DI KOTA PROBOLINGGO - Aisatur Rodyah; Lailiyatus Zahro; Alya Ely Ni’Maizah; Muhammad Nabat Ardli (Wasīlah: Journal Of Sharia Sciences, 2026)
The practice of selling doctor-compounded skincare products without a distribution permit from the Indonesian Food and Drug Authority (BPOM) remains common, particularly among Generation Z consumers who seek rapid skincare results. This practice raises concerns regarding product safety, quality, and legal compliance. This study aims to analyze the practice of selling doctor-compounded skincare products without BPOM distribution permits to Generation Z consumers in Probolinggo City and examine it from the perspective of Islamic Economic Law. A qualitative field research approach was employed. Data were collected through interviews with three Generation Z consumers, a natural skincare expert who is also an MSME entrepreneur, and a law lecturer, then analyzed using descriptive qualitative analysis. The findings reveal that consumers were influenced by expectations of instant results, recommendations from others, and social media exposure. Most informants lacked awareness of the products’ legal status before use and reported side effects such as irritation, burning sensations, skin thinning, and dependency. From the perspective of Islamic Economic Law, this practice contains elements of gharar due to uncertainty regarding legality and safety, and dharar because of potential health risks. Therefore, it contradicts the principles of honesty, responsibility, maslahah, and consumer protection.